CHARACTERISTICS OF THE AUDIT COMMITTEE AND BOARD OF DIRECTORS: HOW DO THEY INFLUENCE CORPORATE SOCIAL RESPONSIBILITY - Arief Nurhandika; Lia Dwi Martika; Yudi Febriansyah (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This research aims to examine the influence of the characteristics of the audit committee and board of directors on CSR scores. This article develops from various literature reviews regarding the relationship between the characteristics of the audit committee and the board of directors on CSR scores. This research uses all company sectors on the Indonesian Stock Exchange except financial sector companies. A purposive sampling was used, and a sample of 78 companies with a total sample data of 468 from 2018-2023 was used. Testing the data using STATA software. The research results show that independent audit committee members have an influence on CSR scores, the size of the audit committee has an influence on CSR scores, audit committee members who have financial expertise influence CSR scores, the size of the board of directors influences CSR scores, and gender diversity has an influence on CSR score. Except for the meeting variable, members of the board of directors do not influence the CSR score.